Prevalence of Pre-Pregnancy Obesity and Its Relationship with Sociodemographic Characteristics in Jordan - Milhem, Aseel; Zaireena, Nur; Faraheen, Nur; Umaisara, Nadeeya Ayn (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study investigates the sociodemographic factors influencing pre-pregnancy body mass indeks (BMI) among Jordanian women, aiming to identify at-risk groups and inform tailored public health strategies. Methodology: A cross-sectional design was employed to analyze pre-pregnancy BMI of a representative sample from two major hospitals. Participants completed a structured questionnaire assessing sociodemographic factors, including age, income, education, employment status, smoking status, and obstetric history. BMI was calculated using self-reported height and weight, with statistical analyses identifying relationship between pre-pregnancy BMI and these variables. Results: The study found that 47.0% of pregnant women were classified as obese, while 17.2% were overweight, and only 34.3% had a normal weight. Significant correlations were identified between pre-pregnancy BMI and age (r = 0.307, p < 0.001), parity number (r = 0.269, p < 0.001), and previous cesarean sections (r = 0.131, p = 0.017). Value: These findings highlight the high prevalence of obesity among pregnant women in Jordan and underscore the need for targeted public health interventions to improve maternal health outcomes.